Sistem Pendukung Keputusan Pemilihan Induk Ikan Gurami Berkualitas Menggunakan Metode AHP - Nuraini Nuraini; Devita Purwiyani (Hemispheres Press, 2023)
Gourami (Osphronemus Gourami) is a fish native to Indonesian waters which is quite well known and in demand in Indonesia. So many enthusiasts are looking for quality carp. To get quality gouramy, quality sires are also needed. In determining the criteria for quality gourami broodstock, a decision support system is needed using the Analytical Hierarchy Process (AHP) method. This method uses selection on existing criteria and determines a suitable solution to the alternative choices. This Decision Support System was built to facilitate field extension officers in determining quality gouramy broodstock. The several criteria obtained for quality gouramy broodstock were age, length, weight, fecundity and egg diameter. The results of this system are recommendations for gourami broodstock